Genetic polymorphisms in FSHR/ALUI and ESRα /BG1I loci and their association with repeat breeder incidence in buffalo - FOUDA, M.; HEMEDA, S.; EL-BAYOMI, K.; EL-ARABY, I.; HENDAM, B.; ATEYA, A. (Journal of the Hellenic Veterinary Medical Society, 2021)
The objectives of this study were to explore the association between FSHR and ESRα genes polymorphism and repeat breeder incidence in Buffalo. DNA was extracted from 243 (96 normal fertile and 147 repeat breeder) Egyptian buffaloes. PCR-AluIof 306-bp of FSHR gene yielded two digested (243 and 63 bp) fragments for the genotype CC, four fragments (243, 193, 63, and 50 bp) for the genotype CG and three fragments (193, 63, and 50 bp) for the genotype GG. Logistic regression analysis presented a significant association of C and G alleles with the incidence of repeat breeder; where the G allele showed a significantly higher incidence compared to C allele in repeat breeder heifers. DNA sequencing of 306 bp of theFSHR gene confirmed the polymorphic patterns attained by RFLP analysis; where C/G SNP was detected and changed threonine into serine amino acid. PCR-RFLP/Bg1I of 248-bpfromtheESRα gene revealed one monomorphic GG genotype (171, 77 bp) confirmed by DNA sequencing. There were no detected SNPs in all enrolled animals. The results herein suggest the effectiveness ofFSHR/AluIlocus polymorphism as a candidate for the incidence of repeat breeder in buffalo thanESRα/Bg1I one results in marker-assisted selection (MAS) against infertile animals.